DNA Configuration in the Core of Marek's Disease Virus - Nazerian, K. (1974)
Marek's disease virus DNA appears to be wound around a central structure connecting the two inner poles of the capsid. Based on electron micrographs of Marek's disease virions, a diagram of spatial configuration of virus DNA is presented. This diagram may explain the pleomorphic character of the herpesvirus core observed with the electron microscope.